2010
DOI: 10.1108/00368791011076227
|View full text |Cite
|
Sign up to set email alerts
|

Study of two‐lobe four recessed hybrid journal bearing

Abstract: Purpose -In recent years, researchers have focused a great deal of attention on multirecess hybrid journal bearing systems. The non-circular journal bearings are widely used in industry on account of their better stability, simplicity, efficiency and low cost. The purpose of this paper is to present a theoretical investigation into the performance of a two-lobe multirecess hybrid journal bearing system. Design/methodology/approach -The Reynold's equation governing the lubricant flow in the clearance space betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…The fluid film thickness for geometrically imperfect four-lobe hybrid journal bearing is expressed in the nondimensional form as 12,25,26 where, h¯ir is contribution of geometric irregularities of journal to the fluid film thickness (h¯) 19 where, a 1 , a 2 and a 3 are the amplitude of irregularities associated with cylindrical journal in the form of barrel, bellmouth and undulation type, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluid film thickness for geometrically imperfect four-lobe hybrid journal bearing is expressed in the nondimensional form as 12,25,26 where, h¯ir is contribution of geometric irregularities of journal to the fluid film thickness (h¯) 19 where, a 1 , a 2 and a 3 are the amplitude of irregularities associated with cylindrical journal in the form of barrel, bellmouth and undulation type, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ghosh and Satish 10,11 theoretically evaluated the stability and rotordynamic coefficients over a range of offset factor (0.5, 0.75, 1, 1.25 and 1.5) for four-lobe bearing. Jain et al 12 investigated the influence of offset factor through a comparative study on the two lobe and circular bearing configuration. Goenka and Booker 13 theoretically examined the influence of surface ellipticity on dynamically loaded cylindrical bearing and suggested an optimum shape of bearing on the basis of fluid film pressure and fluid film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…Research studies [6][7][8][9][10][11][12][13][14] in the area of non-circular bearings are discussed below. Non-circular bearings (two-lobe, three-lobe and four-lobe bearings) were examined by Rahmatabadi et al 6 They evaluated various static characteristics of these bearings and compared them.…”
Section: Introductionmentioning
confidence: 99%
“…They used Generalized Differential Quadrature technique to solve Reynold's equation and suggested that proper selection of tilt angle results in improved performance. The performance of a twolobe four recessed hybrid journal bearing was evaluated by Jain et al 13 Author observed that there was an enhancement in the performance of such bearing as compared with a circular recessed journal bearing system. They suggested that proper selection of bearing offset factors leads to improved performance.…”
Section: Introductionmentioning
confidence: 99%
“…There are number of studies available in literature pertaining to multilobe and circular journal bearing, both analytical and experimental. [1][2][3][4][5][6][7][8] The journal surfaces obtained after machining are not really perfectly cylindrical or smooth. The actual machined surface of the journal may be associated with different types of periodic surface disturbance (waviness) which are also referred to as geometric irregularities.…”
Section: Introductionmentioning
confidence: 99%